CEO’s Characteristics and CSR Disclosure: Evidence from Islamic Banks across MENA Region - Jamel Chouaibi,; Wafa Jilani,; Salim Chouaibi, (Asian Academy of Management Journal, 2023)
The purpose of this paper was to explore the relationship between the characteristics of the chief executive officer (CEO) and corporate social responsibility (CSR) of banks operating in the Middle East and North African (MENA) countries. The study hypotheses was tested using a multiple linear regression model by examining data from a sample of 97 Islamic banks operating in the MENA region between 2015 and 2019. The results were robustly checked and the findings indicated that both CEO’s overconfidence, experience and education appear to have a significantly positive effect on the CSR disclosure. Furthermore, the results of multiple linear regressions showed that older CEO’s have a negative and significant impact on the level of CSR disclosure. This research bridges the gap between theory and practice in many aspects. Thus, although a substantial volume of research has examined sustainable advantage, one vital aspect of CSR has been largely unexplored. This study fills this void in the literature, namely the interaction between CEO’s characteristics and CSR disclosure. An explicit CSR disclosure may improve social well-being in emerging markets.